Electron circular dichroism in hot electron emission from metallic nanohelix arrays - Nürenberg, Daniel; Mark, Andrew G.; Fischer, Peer; Zacharias, Helmut (The journal of chemical physics, 2023)
We investigate the electron emission from 3D chiral silver alloy nanohelices initiated by femtosecond laser pulses with a central photon energy of hν = 1.65 eV, well below the work function of the material. We find hot but thermally distributed electron spectra and a strong anisotropy in the electron yield with left- and right-circularly polarized light excitations, which invert in sign between left- and right-handed helices. We analyze the kinetic energy distribution and discuss the role of effective temperatures. Measurements of the reflectance and simulations of the absorbance of the helices based on retarded field calculations are compared to the anisotropy in photoemission. We find a significant enhancement of the anisotropy in the electron emission in comparison to the optical absorption. Neither simple thermionic nor a multiphoton photoemission can explain the experimentally observed asymmetries. Single photon deep-UV photoemission from these helices together with a change of the work function suggests a contribution of the chirally induced spin selectivity effect to the observed asymmetries.
Online veröffentlicht: 28. Juli 2023
Gesehen am 28.09.2023